Association between maternal exposure to cumulative childhood trauma and offspring childhood trauma and depressive symptoms among Chinese adolescents - Yaru Zhang; Yuqiong He; Zhenpeng Xue; Jianchang Xu; Yumeng Sun; Shiqi Song; Ling Lin; Jianping Lu; Xuerong Luo; Jianbo Liu (BMC Public Health)
Abstract Background This study aimed to explore the effect of maternal exposure to cumulative childhood trauma (CT) on offspring CT and depressive symptoms. Methods A total of 3672 mothers and their 3672 adolescent offspring who completed the questionnaires were included in this study. CT was assessed using the Childhood Trauma Questionnaire Short Form, while depressive symptoms in adolescents were assessed using the Center for Epidemiological Studies Depression Scale. Results Among the 3672 maternal respondents, 1397 (38.04%) reported ever having experienced CT and 463 (12.61%) reported ≥ 2 types of CT. As shown by logistic regression analysis, having a mother who was exposed to 1 or ≥ 2 types of CT was a risk factor for offspring CT exposure in the overall sample of adolescents, as well as male and female adolescent subgroups, relative to those whose mothers were not exposed to CT. Offspring emotional neglect mediated the relationship between maternal exposure to cumulative CT and offspring depressive symptoms among male and female adolescents, while offspring physical neglect mediated the relationship between maternal exposure to cumulative CT and offspring depressive symptoms among male adolescent offspring, as the indirect paths did not include 0. Conclusion Maternal exposure to cumulative CT may affect the severity of CT in their adolescent offspring, which indirectly impacts adolescents’ depressive symptoms.